Factors of Acceptance and Use of the Merdeka Mengajar Platform and Its Influence on Teachers' Professional Competence - Kunto Aji Utomo; Slamet Lestari (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
Teachers have accessed the PMM, but not all features have been utilized, resulting in the platform's full potential not being fully realized. This study aims to analyze the acceptance and use factors of the Merdeka Mengajar (PMM) Platform and its impact on teacher professional competence using the Unified Model of Electronic Government Adoption (UMEGA). The method used was quantitative with an ex-post facto design, and the sampling technique was proportional cluster random sampling involving 105 teachers. Data were collected through questionnaires. The data analysis technique used was Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS V.4.0.0.9. The results showed that performance expectations positively and significantly affected attitudes towards using PMM by 43.5%. Effort expectations had a positive but insignificant effect on attitudes towards using PMM by 10.0%. Social influence positively and significantly affected attitudes towards using PMM by 19.5%. Facilitating conditions had a positive but insignificant effect on behavioral intentions towards using PMM by 14.5%. Facilitating conditions positively and significantly affected expectations towards using PMM by 65.9%. Perceived risk has a negative and significant effect on individual attitudes regarding the use of PMM by -25.4%. Attitudes toward the use of PMM have a positive and significant effect on behavioral intentions to use PMM by 72.7%. Intentions to use PMM positively and significantly affect behavioral intentions to use PMM by 55.4%. Behavioral intentions to use PMM have a positive but insignificant effect on teacher professional competence by 24.8%.